2023
DOI: 10.2174/1871520623666230220152833
|View full text |Cite
|
Sign up to set email alerts
|

JDHY3 Inhibits Hypopharyngeal Carcinoma Cell Proliferation and Promotes Apoptosis by Inhibiting the PI3K/AKT Pathway

Abstract: Background: Jieduhuayu No.3 (JDHY3) is a modified Chinese herbal formula beneficial for treating hypopharyngeal carcinoma (HC), but its pharmacological mechanism is unknown. Objective: This study aimed to explore the mechanism of the herbal formula JDHY3 in inhibiting cell proliferation and promoting apoptosis in HC in vitro and in vivo. Methods: In this study, HC cells were treated with cisplatin and different concentrations of JDHY3. The apoptosis rate was detected by flow cytometry. Western blotting was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…The PI3K/Akt signaling pathway is a key signal mechanism in the biological process of mammals that is involved in cell growth, proliferation, apoptosis, migration, and other physiological or pathological processes 10 , 11 , 12 , 13 . It has been confirmed that activation of the PI3K/Akt signaling pathway can effectively reduce oxidative stress 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K/Akt signaling pathway is a key signal mechanism in the biological process of mammals that is involved in cell growth, proliferation, apoptosis, migration, and other physiological or pathological processes 10 , 11 , 12 , 13 . It has been confirmed that activation of the PI3K/Akt signaling pathway can effectively reduce oxidative stress 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%